Pourquoi croire au modèle du développement territorial au Maghreb ? Une approche critique - Kirsten Koop; Pierre-Antoine Landel; Bernard Pecqueur (EchoGéo)
Since decolonisation, a succession of development models has been transferred from France towards North African countries. The failure of the industrial development approach on national level opened the way for local development in the late 1980’s, and the power of globalisation dynamics recently gave birth to the “territorial development” model. This new approach towards (economic) development and local governance is actually transferred into regional planning practices of Morocco, Tunisia and Algeria on behalf of several French cooperation programs. We here question the relevance of the application of the concept of territory in these North African countries - a concept which turned out to be a central one in French regional planning politics. We particularly analyse the two preconditions for the revealing of specific territorial resources: the decentralisation processes of North African public policies and the capacity of local actors to participate at territorial governance systems.